2007
DOI: 10.1007/s10495-007-0152-y
|View full text |Cite
|
Sign up to set email alerts
|

Iridovirus Bcl-2 protein inhibits apoptosis in the early stage of viral infection

Abstract: The grouper iridovirus (GIV) belongs to the family Iridoviridae, whose genome contains an antiapoptotic B-cell lymphoma (Bcl)-2-like gene. This study was carried-out to understand whether GIV blocks apoptosis in its host. UV-irradiated grouper kidney (GK) cells underwent apoptosis. However, a DNA fragmentation assay of UV-exposed GK cells after GIV infection revealed an inhibition of apoptosis. The UV- or heat-inactivated GIV failed to inhibit apoptosis, implying that a gene or protein of the viral particle mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…It was previously shown that GIV66 is localized at the outer mitochondrial membrane and was able to inhibit Bcl-2 mediated apoptosis in UV irradiated GK cells (27), however no detailed mechanism was proposed to rationalize these findings. To understand the molecular mechanism of action and structural basis of GIV66 mediated inhibition of apoptosis we recombinantly expressed and purified GIV66 to perform Isothermal Titration Calorimetry (ITC) with peptides spanning the BH3-motif of pro-apoptotic Bcl-2 proteins.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was previously shown that GIV66 is localized at the outer mitochondrial membrane and was able to inhibit Bcl-2 mediated apoptosis in UV irradiated GK cells (27), however no detailed mechanism was proposed to rationalize these findings. To understand the molecular mechanism of action and structural basis of GIV66 mediated inhibition of apoptosis we recombinantly expressed and purified GIV66 to perform Isothermal Titration Calorimetry (ITC) with peptides spanning the BH3-motif of pro-apoptotic Bcl-2 proteins.…”
Section: Resultsmentioning
confidence: 97%
“…Iridoviruses and chloriridoviruses commonly infect invertebrates whereas ranaviruses and lymphocystivirus target vertebrates including amphibians, fish and reptiles. The sequencing of the grouper iridovirus genome revealed the presence of a putative Bcl-2 like protein (26), GIV66, and functional studies established that GIV66 locates to the outer mitochondrial membrane and is able to inhibit UV induced apoptosis in grouper kidney cells (27). However, the molecular and structural basis of apoptosis inhibition by GIV66 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These putative immune evasion proteins include the aforementioned viral homolog of eIF-2α (vIF-2α), a viral homolog of RNAse III, a virus-encoded CARD (caspase activation and recruitment domain)-containing protein, a viral homolog of steroid dehydrogenase (β-HSD), a viral Bcl-2 homolog, and one or more TNFR homologs (Huang et al 2013b ;Lin et al 2008 ;Tan et al 2004 ). In addition to these putative immune effectors, there are other viral genes that are unique to specifi c viruses or genera and may represent proteins that act only within specifi c host species, tissues, or cells.…”
Section: Interplay Between Host and Virus Determines The Outcome Of Imentioning
confidence: 99%
“…As an aquatic virus, iridovirus was increasingly taken into account because it caused heavy economic losses in farmed food and ornamental fish, as well as posed great threat to wildlife conservation. The researches about iridovirus focused on complete sequence determination (Eaton et al, 2007;Huang et al, 2009;Jancovich et al, 2010;Shi et al, 2010;Wong et al, 2011;Zhang et al, 2004), transcriptome and proteome analysis Dang et al, 2007;Ince et al, 2010;Luo et al, 2009;Majji et al, 2009;Song et al, 2006) and individual gene identification (Ao and Chen, 2006;Lin et al, 2008;Wan et al, 2010;Wang et al, 2008;Zhao et al, 2007Zhao et al, , 2008b, such as RGV thymidine kinase (TK) gene and envelope protein 53R. TK gene, an early gene of RGV, exists in many large DNA viruses and encodes a cytoplasmic protein .…”
Section: Introductionmentioning
confidence: 99%